Neurophysiological effects of altruistically motivated craft activities in occupational therapy: A pilot study using frontal EEG and heart rate variability analysis - Junya Orui; Keigo Shiraiwa; Takao Inoue; Masaya Ueda; Keita Ueno; Yasuo Naito; Ryouhei Ishii (Hong Kong Journal of Occupational Therapy)
Introduction Occupational therapy utilizes altruistically motivated activities, potentially influencing both frontal alpha asymmetry (FAA) associated with approach motivation and autonomic responses. This study examines the effects of altruistically motivated craft activities on FAA and autonomic activity. Methods Fifteen rehabilitation students (21.0 ± 0.4 years) performed a netcraft task under altruistic and selfish conditions. EEG and ECG were measured during the craft task, and FAA and autonomic indices were analyzed. Results FAA score was significantly higher in the altruistic condition ( p = .040, d = 0.59), indicating increased approach motivation. Sympathetic activity was significantly lower in the altruistic condition ( p = .018, r = −0.68), indicating reduced sympathetic activity. Conclusions Altruistically motivated craft activities increased relative left frontal cortical activity and decreased sympathetic activity, highlighting their potential benefit in occupational therapy. These findings are not only consistent with previous research, but also support the inclusion of altruistic activities in therapeutic interventions to improve mental health and well-being.